A Comparative Study of Developmental Mathematics Pass Rates for Two Student Groups: Emporium Classes and Traditional Lecture-based Classes - Wang, David (International Journal Of Chemistry, Mathematics And Physics(IJCMP), 2022)
Since the turn of the 21st century, the emporium model has become a popular choice for colleges and universities to reform developmental mathematics. The purpose of this study is to determine overall how successful Northeast Metro College (NMC)’s emporium developmental mathematics program is as compared to its traditional lecture-based program by comparing these two programs’ student pass rates in developmental courses. This research is a non-experimental, secondary data quantitative analysis study with nonrandom convenience samples. The findings indicate that generally emporium classes prepare students for passing developmental mathematics more successfully than traditional lecture-based classes do.